Pediatric tuberculosis in Turkey: a review of 8-years period in a tertiary care hospital - Bayhan, Gulsum Iclal; Tanir, Gonul; Metin, Ozge; Simsek, Hulya; Aydin-Teke, Turkan; Oz, Fatma Nur; Aydin, Zeynep Gokce Gayretli (Turkish J Pediatrics, 2015)
The purpose of this study was to evaluate the clinical, radiological, microbiological characteristics, side effects of anti-TB drugs and treatment outcome of childhood definite or probable TB. The medical records of all childhood TB patients were investigated in the department of pediatric infectious disease of a tertiary care hospital between January 2005 and December 2012. Patients who followed-up until the anti-TB treatment was completed were included in the study. One hundred forty four pediatric cases with active TB were included in the study (27 definite, 117 probable). Twenty-four (16.7 %) patients were asymptomatic at admission. Pulmonary TB was the most common type. The most common localizations for extrapulmonary TB were superficial lymphadenitis. An index case was detected in 39.6% of the patients. In conclusion, the absence of constitutional symptoms does not exclude TB. Household contact screening plays an important role in the diagnosis of childhood TB especially in asymptomatic patients.
Keywords: childhood; Mycobacterium tuberculosis; lymhadenopathy; chest X-ray; computedtomography